1996
DOI: 10.1046/j.1365-2249.1996.d01-718.x
|View full text |Cite
|
Sign up to set email alerts
|

Soluble products of inflammatory reactions are not induced in children with asymptomatic Plasmodium falciparum infections

Abstract: SUMMARYA proportion of children with Plasmodium falciparum infection have a high parasitaemia without accompanying fever, indicative of different clinical thresholds of parasitaemia. Higher levels of IL-10, IL-1Ra and sIL-4R but not sIL-2R were found in children with P. falciparum malaria, compared with levels in children with asymptomatic P. falciparum infections and in healthy children. Concentrations of IL-10 and IL-1Ra were correlated with levels of parasitaemia, but the association of cytokine levels with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 11 publications
2
10
0
Order By: Relevance
“…In man, a role for aPL in antimalarial immunity has been proposed in several studies [6,14,15]. An attractive explanation consists of inhibition of mechanisms leading to TNF‐α production, especially during severe malaria [45,46]. In the present study, definite association was found between aPL and clinical/endemic statuses of donors.…”
Section: Discussionsupporting
confidence: 62%
“…In man, a role for aPL in antimalarial immunity has been proposed in several studies [6,14,15]. An attractive explanation consists of inhibition of mechanisms leading to TNF‐α production, especially during severe malaria [45,46]. In the present study, definite association was found between aPL and clinical/endemic statuses of donors.…”
Section: Discussionsupporting
confidence: 62%
“…Typically, they were found elevated in long-term exposed subjects and in acute symptomatic infection, while asymptomatic infection has rarely been studied. However, phospholipid-related specificities were found more elevated in asymptomatics than in patients with malaria symptoms [29,30]. All these previous studies focused on antibody specificities otherwise known from autoimmune disease conditions, particularly systemic lupus erythematosus.…”
Section: Discussionmentioning
confidence: 99%
“…In children with acute disease, the concentrations of TNF-␣, IL-12, and IL-10 in plasma did not correlate with each other. The plasma concentration of IL-10 was positively correlated with parasitemia (14) and the number of BDCA3 ϩ mDCs in children with acute malaria (Pearson correlation coefficient: parasitemia, r ϭ 0.794, P Ͻ 0.001; BDCA3 ϩ mDC, r ϭ 0.393, P Ͻ 0.05). The concentration of IL-12 or TNF-␣ in plasma did not correlate with the absolute number of or HLA DR expression on any of the DC subsets or monocytes.…”
Section: Frequency Of Peripheral Blood DC Subsetsmentioning
confidence: 98%